Resposta dos manguezais do Amapá, Rio Grande do Norte, Sul da Bahia e Espírito Santo às mudanças climáticas e flutuações do nível do mar durante o holoceno - ALVES, Igor Charles Castor (Universidade Federal do Pará, 2017)
The present work integrates geomorphological, sedimentological, and palynological data with radiocarbon dating, as well as δ13C, δ15N, and C/N from sedimentary organic matter from Amapá, Rio Grande do Norte, Sul da Bahia e Espírito Santo. Along the northern littoral, the area occupied by mangroves and marine influenced were larger than today, between >8750 and ~2250 cal yr BP., forming a continuous mangrove belt. However, mangroves were replaced by freshwater vegetation in areas influenced by the Amazon River discharge during the late Holocene. The elevated tidal flats occupied by herbs indicate a transition from marine influence with mangroves to a phase dominated by herbs and terrestrial organic matter at about 400 cal yrs BP. During the last decades have occurred a mangrove migration trend to more elevated surfaces. The mangroves from the Ceará-Mirim River, Rio Grande do Norte, have occurred within the modern tidal range since ~7000 cal yrs BP, and was not found indications of marine influence above the modern tidal range. However, studies developed 34 km upriver on Jucuruçu River, Prado-Bahia, indicate mangroves and estuarine organic matter between ~7400 and ~5300 cal yrs BP. During the late Holocene, the mangroves migrated to the mouth of this river. Similar dynamic was identified along the Linhares littoral, Espírito Santo, where the upper limits of tidal flats were dominated by mangroves during the middle Holocene, followed by beach ridges progradation over mangrove muddy layers during the late Holocene. During the last centuries the mangroves have established over herbaceous plains with an increase trend of estuarine organic matter. Regarding the mangrove dynamic from Northern Brazil, the sea level rise and the lower Amazon fluvial discharge during the early and middle Holocene caused the development of a continuous mangrove line. It was fragmentated during the late Holocene due to the increase of river freshwater discharge that caused a significant decrease of tidal water salinity in areas near the mouth of Amazon River. The mangrove migration to lower zones since ~400 cal yrs BP was followed by an inverse displacement during the last decades. It was caused by a relative sea level fall in a century time scale and a relative sea level rise in a decadal time scale. In the Rio Grande do Norte littoral, the mangrove establishment was basically controlled by the post-glacial sea level rise up ~7000 cal yrs BP, when it reached its modern level. However, in Prado, southern Bahia littoral, and Linhares, Espírito Santo, mangroves migrated to higher surface according to sea level rise until 2.7 m above the modern Relative Sea Level-RSL, together with a decrease of fluvial discharge at about 5300 cal yrs BP. Later, the RSL decreased to its modern level and occurred an increase of fluvial discharge during the late Holocene. During the last centuries, the mangroves from Linhares may have reacted to a relative sea level rise. Based on these data, is possible to anticipate the mangrove dynamic until the end of century XXI. Considering RSL rises, probably, the mangrove areas along the Brazilian littoral will shrink by its drowning. Regarding the north, northeast and southeastern littoral, even with a RSL rise tolerable by mangroves, the consequences of the RSL rise to mangroves will depend on topographic surface available to its migration and climatic conditions. The geomorphologic and climatic setting more damaging to mangrove is one with a limited coastal plain suitable for mangrove migration under a RSL rise associated to an increase of fluvial discharge. In this situation, besides the mangroves are being drowned by a sharp topographic transition between the coastal plateau and the coastal plain, there would be no possibility of mangrove displacement within the estuarine valleys and deltaic plains, because the increase of fluvial discharge would hamper the development of tidal plains with appropriate pore water salinities to establishment and survival of mangroves.